2011
DOI: 10.1891/1946-6560.2.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Top 10 Reasons Why Women’s Perpetration of Intimate Partner Violence Is an Important Area of Inquiry

Abstract: Women's perpetration of intimate partner violence (IPV) has been an extremely controversial topic. In this article, the author discusses 10 reasons why it is critically important to study women's use of IPV. The prevalence and motivation of women's use of IPV are discussed, as well as the psychopathology typically found in clinical samples of female IPV perpetrators. Consequences of women's IPV for victims, for romantic relationships, for witnessing children, and for the female perpetrators themselves are revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 87 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…Studies have indicated that women who engage in IPA often report severe and traumatic experiences of sexist discrimination in the form of gender-based violence (Fortunata & Kohn, 2003; Hamberger & Larsen, 2015; Leisring, 2011; Morrison et al, 2007). The term gender-based violence refers to traumatic events (e.g., sexual assault, rape, interpersonal violence) that are experienced at greater rates by individuals with oppressed gender identities and that reinforce patriarchal structures (Heise et al, 1999).…”
Section: Sexist Discrimination and Ipamentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have indicated that women who engage in IPA often report severe and traumatic experiences of sexist discrimination in the form of gender-based violence (Fortunata & Kohn, 2003; Hamberger & Larsen, 2015; Leisring, 2011; Morrison et al, 2007). The term gender-based violence refers to traumatic events (e.g., sexual assault, rape, interpersonal violence) that are experienced at greater rates by individuals with oppressed gender identities and that reinforce patriarchal structures (Heise et al, 1999).…”
Section: Sexist Discrimination and Ipamentioning
confidence: 99%
“…The term gender-based violence refers to traumatic events (e.g., sexual assault, rape, interpersonal violence) that are experienced at greater rates by individuals with oppressed gender identities and that reinforce patriarchal structures (Heise et al, 1999). Research suggests that the vast majority of women receiving treatment for using IPA have experienced interpersonal traumas, including IPA victimization, witnessing IPA as a child, sexual assault, and other violent crime victimization (Leisring, 2011; Miles-McLean et al, 2019; Swan et al, 2018). In fact, some evidence indicates that women receiving treatment for IPA report higher levels of sexual assault than women receiving treatment for IPA victimization (Abel, 2001).…”
Section: Sexist Discrimination and Ipamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is essential to examine posttraumatic stress among this highly prevalent but understudied population. Doing so may enhance the representativeness and generalizability of findings and their implications for future research and interventions (Leisring, ).…”
mentioning
confidence: 99%